2023
DOI: 10.1186/s40066-022-00401-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate-smart agriculture adoption on food security and multidimensional poverty of rural farm households in the Central Rift Valley of Ethiopia

Abstract: Background Climate change has perverse effects on the natural resource base and agricultural productivity, negatively affecting the well-being of households and communities. There are various attempts by the government and NGOs to promote climate-smart agricultural (CSA) practices to help farmers adapt to and mitigate these negative impacts. This study aimed to identify CSA practices widely adopted in the study area and examined their impacts on rural farm households’ food security and multidim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 41 publications
(66 reference statements)
0
17
0
2
Order By: Relevance
“…This was done by merging the household and plot-level GPS coordinates with the Africa Rainfall Climatology version 2 (ARC2) of the National Oceanic and Atmospheric Administration's (NOAA) database. 2 Daily time series rainfall and temperature data were extracted for the period 1983-2017. Focusing on the planting season months (March-June), coefficient of variation of temperature, rainfall, and growing degree days (GDD) and average rainfall shortfall were generated and included as additional covariates in the adoption and intensity of adoption models.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…This was done by merging the household and plot-level GPS coordinates with the Africa Rainfall Climatology version 2 (ARC2) of the National Oceanic and Atmospheric Administration's (NOAA) database. 2 Daily time series rainfall and temperature data were extracted for the period 1983-2017. Focusing on the planting season months (March-June), coefficient of variation of temperature, rainfall, and growing degree days (GDD) and average rainfall shortfall were generated and included as additional covariates in the adoption and intensity of adoption models.…”
Section: Datamentioning
confidence: 99%
“…There are a number of theoretical and empirical studies on the adoption of SAPs [2,10,14,17,26,37,46]. There are equally a few recent studies in this area focusing specifically on Nigeria [3,6,28,40] and others on agricultural productivity [9,38].…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of sampling procedure and sample size determination of the study is found in Ali et al. (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Well‐structured and pretested questionnaire was used for the data collection. A complete description of types of data and method of data collection is presented in (Ali et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…security, measured in terms of food consumption score and dietary diversity score. Moreover, CSA can raise food security by raising crop productivity and reducing the risk of crop failure by mitigating the adverse impacts of climate change"[16].…”
mentioning
confidence: 99%